2017
DOI: 10.1111/1471-0307.12381
|View full text |Cite
|
Sign up to set email alerts
|

Comparative stability of aspartame and neotame in yoghurt

Abstract: The comparative stability of aspartame and neotame was monitored in yoghurt during its processing, fermentation and storage. A solid-phase extraction method was suggest changing it to developed for the isolation of aspartame and neotame. Pasteurisation (85°C/30 min) resulted in approximately 47% and 3% loss of aspartame and neotame, respectively. During fermentation, 3% loss of aspartame was observed, but no loss of neotame. There was no significant effects on the stability of either aspartame or neotame durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Streptococcus thermophilus and Lactobacillus delbrueckii spp. Bulgaricus is 2 LAB present in yoghurt starter culture that converts milk into gel curd (Kumari et al., 2018). Successive lactic acid production lowers the milk pH, and the micelle casein loses its tertiary structure due to the protonation of the amino acid residues.…”
Section: Introductionmentioning
confidence: 99%
“…Streptococcus thermophilus and Lactobacillus delbrueckii spp. Bulgaricus is 2 LAB present in yoghurt starter culture that converts milk into gel curd (Kumari et al., 2018). Successive lactic acid production lowers the milk pH, and the micelle casein loses its tertiary structure due to the protonation of the amino acid residues.…”
Section: Introductionmentioning
confidence: 99%
“…14 NEO with higher sweetness may be widely used, e.g., NEO has been found in 41.0% of the feed samples at concentrations of 0.1-70.0 mg kg -1 [35]. Kumari et al (2018) confirmed that NEO exhibited better stability than ASP in yoghurt [36]. Thus, with the further promotion and use of NEO in food, the detection concentration of NEO in the sewage treatment plant will continue to increase, whether NEO can be used as a tracer for wastewater requires further research.…”
Section: Artificial Sweeteners In Effluent Of Wwtpsmentioning
confidence: 99%
“…The sweetener does not include any neotame calories and has a sweetness factor of approximately 7.000-13.000 times greater than sucrose and 30-60 times greater than aspartame [1]. While neotame has approximately the same stability as aspartame in the acidic pH range (pH 3-5.5), neotame at neutral pH is significantly more stable than aspartame [2][3][4]. Dimethyl butyl (DMB), contained in the chemical structure of neotame, provides unique properties such as significantly improved sweetening power, flavor-enhancing properties, and stabilization during cooking or pasteurization [5].…”
Section: Introductionmentioning
confidence: 99%
“…The DMB group restricts the reactivity of the dipeptide amino group; therefore, no cyclization occurs unlike aspartame [6]. The absence of cyclization significantly increases neotame stability in the neutral pH compared to aspartame, hence offers possibilities for neotame in new applications that are not directly accessible for aspartame [4,[7][8][9]. Also, the 3,3-dimethyl butyl group effectively restricts the peptidase effect on the dipeptide bond by secreting phenylalanine, which in turn reduces the production of phenylalanine and the anxiety of phenyl ketone urics [10,11].…”
Section: Introductionmentioning
confidence: 99%